RUSSELL’S VIPER SNAKE ENVENOMATION IN A DOG: A CASE REPORT - B.K. Bhagya; V. Shivakumar; M. Shivakumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A three year old, male, Dachshund dog, weighing 10 Kg was presented to Veterinary College Hospital, Hassan with the history of snake bite (Russell’s viper). On physical examination, animal was dull and depressed, face was swollen and fang marks were observed on the right side of the face and blood tinged fluid was oozing from the bitten area. Animal was evincing pain on palpation of swollen area. Haemato-biochemical findings were within the normal range except for thrombocytopenia. The case was diagnosed as snake envenomation and treated with polyvalent anti snake venom intravenously, along with 100 ml of 0.9 per cent normal saline, dexamethasone and antibiotics for 5 days. Animal made uneventful recovery after 5 days of treatment.